Changes in Positive and Negative Affect during Acute Psychiatric Treatment in People with Social Anxiety Disorder - Bowers, Emily M.; Peckham, Andrew D.; Goodman, Fallon R.; Hom, Melanie A.; Beckham, Erin; Björgvinsson, Thröstur; Beard, Courtney (Depression and Anxiety, 2023)
People with social anxiety disorder (SAD) experience less positive affect (PA) and more negative affect (NA) than the general population, a pattern more similar to depression than other anxiety disorders. There is a dearth of research assessing whether PA is targeted effectively during treatment, even though this is an important emotional aspect for quality of life. The primary aim of this study was to examine daily changes in self-report PA and NA among a sample of partial hospital program (PHP) patients with SAD. A secondary aim was to examine baseline depression severity as a moderator of daily PA and NA change. Patients were adults (N=241) diagnosed with SAD seeking treatment at a typically 1–2-week transdiagnostic behavioral health PHP from September 2017 to September 2019. Patients completed (1) the International Positive and Negative Affect Schedule-Short Form (IPANAS-SF) each treatment day to assess affect and (2) the Patient Health Questionnaire-9 Item Version (PHQ-9) at baseline to assess depressive symptoms. Data from the first nine days of treatment were included in analyses: two-level multilevel model (MLM) analyses were used to address study aim 1, and baseline depression severity was added as a moderator to address study aim 2. Patients reported significant decreases in NA but no significant changes in PA over the course of PHP treatment. Additionally, there was no significant evidence of depression moderating NA change; however, depression did moderate PA change. These findings suggest that patients with SAD report significant decreases in NA but no change in PA over transdiagnostic group treatment, with increases in PA being stronger among patients with more severe depressive symptoms. PA captures an important emotional experience for living a fulfilling life, yet CBT-based treatments may not be effectively improving these areas. Future studies targeting PA in SAD treatment can inform whether doing so ultimately improves treatment outcomes for SAD.